1992
DOI: 10.1073/pnas.89.1.290
|View full text |Cite
|
Sign up to set email alerts
|

Replication of single-stranded plasmid pT181 DNA in vitro.

Abstract: Plasmid pT181 is a 4437-base-pair, multicopy plasmid of Staphylococcus aureus that encodes tetracycline resistance. The replication of the leading strand of pT181 DNA initiates by covalent extension of a site-specific nick generated by the initiator protein at the origin of replication and proceeds by an asymmetric rolling circle mechanism. The origin of the leading strand synthesis also serves as the site for termination ofreplication. Replication ofpT181 DNA in vivo and in vitro has been shown to generate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…After one round of replication, the nick site is regenerated, and the initiators make a second cleavage and ligate the displaced SS leading strand of the DNA. The SS DNA is then converted to the double-stranded (DS) form utilizing the single-strand origin (SSO) (Baas and Jansz, 1988;Birch and Khan, 1992;Dempsey et al, 1995;Gruss et al, 1987). Previous studies have shown that the origin of replication contains sequences necessary for both the initiation and termination of RC replication (Dotto et al, 1984;Gros et al, 1987;Murray et al, 1989;Sozhamannan et al, 1990;Iordanescu and Projan, 1988;Zhao and Khan, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…After one round of replication, the nick site is regenerated, and the initiators make a second cleavage and ligate the displaced SS leading strand of the DNA. The SS DNA is then converted to the double-stranded (DS) form utilizing the single-strand origin (SSO) (Baas and Jansz, 1988;Birch and Khan, 1992;Dempsey et al, 1995;Gruss et al, 1987). Previous studies have shown that the origin of replication contains sequences necessary for both the initiation and termination of RC replication (Dotto et al, 1984;Gros et al, 1987;Murray et al, 1989;Sozhamannan et al, 1990;Iordanescu and Projan, 1988;Zhao and Khan, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in ss + dsDNA conversion are not well understood, although some features of the process have been defined. First, it seems that only host proteins are involved in the lagging-strand synthesis, most likely RNA polymerase, as shown in vivo for the ssoU of PUB110 (Boe et al, 1989), and in vitro for the ssoA of pT181 (Birch & Khan, 1992). However, in the case of the lactococcal plasmid pWVOl (an ssoAcontaining plasmid) this conversion has been proposed to be mediated by the host DNA primase (Leenhouts e t al., 1991).…”
Section: Introductionmentioning
confidence: 99%
“…lb). Re&' r i m s similar in size have been defined for the ssoA4 of plasmid pT181 (Birch & Khan, 1992), and for the SJ-OCT o f PUB1 10 (Boe ef a/., 1989). In addition to this, u7e may also conclude that either the DNA sequence or its structure within the RS, plays an important role in the ss -+ d s D N h conversion.…”
Section: Deletion Mapping Of Ssoamentioning
confidence: 99%
See 2 more Smart Citations